Moderating Role of Values in Religiosity and Brand Switching from Israel-Affiliated Brands among Gen Z - Agus Sani; Muhammad Shareza Hafiz; Arif Pratama Marpaung (Journal of Applied Business Administration, 2025)
This study examines the influence of religiosity on Indonesian consumers' brand switching behavior, particularly regarding brands affiliated with the Israeli-Palestinian issue. Using SEM-PLS analysis with 178 respondents obtained through snowball sampling, the results reveal that religiosity positively and significantly affects consumers' tendency to switch from Israeli-affiliated brands to local alternatives. Furthermore, functional, emotional, social, and epistemic values significantly strengthen this relationship. These findings highlight that consumer behavior is influenced not only by economic considerations but also by spiritual, social, and cognitive factors. In today's value-conscious consumer landscape, purchasing decisions increasingly reflect personal and collective beliefs. For marketers, this emphasizes the importance of developing ethical, value-driven branding strategies that resonate with consumers' social and moral awareness. Brands that align with consumer values and demonstrate social responsibility are more likely to foster loyalty and trust in an era where consumers are buying not just products, but also meaning and identity.